Prisoners’ rights under the Nigerian law: legal pathways to progressive realization and protection (2015)
A prisoner is denied certain rights as a result of the custodian judgment passed on him or her by a court of law. A prisoner in custody is specifically subjected to restraint of movement and can, therefore, not have total assurance of enjoyment of the freedom of personal liberty under the law. Be that as it may, a prisoner who is observing the sentence of court by being in custody does not totally lose his rights as a human being and must, therefore, enjoy some basic rights despite being confined to prison. In reality, prisoners are seen as being less of human beings and are not well treated when observing custodian sentence. Some rights are denied the prisoners by the prison administrators and, by extension, the State by lack of will to promote enabling environment and treatment to the prisoners. It is against this backdrop that this article appraises prisoners’ rights that are to be respected, protected and fulfilled under the law, at national, regional and international levels. The article argues that there are certain essential and set global standards for the treatment of prisoners, which are not currently followed in prison administration in Nigeria. This article examines basic fundamental human rights which should not be forfeited as a result of incarceration. It evaluates how such rights fare in the Nigerian prison system, and itemizes practical measures that must be put in place to ensure the protection and fulfilment of these rights in Nigeria.